2022
DOI: 10.3390/jcm11051224
|View full text |Cite
|
Sign up to set email alerts
|

ECMO Predictors of Mortality: A 10-Year Referral Centre Experience

Abstract: Background: Extracorporeal membrane oxygenation (ECMO) is a specialised life support modality for patients with refractory cardiac or respiratory failure. Multiple studies strived to evaluate the benefits of ECMO support, but its efficacy remains controversial with still inconsistent and sparse information. Methods: This retrospective analysis included patients with ECMO support, admitted between January 2010 and December 2019 at a tertiary university ECMO referral centre in Austria. The primary endpoint of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…In the case of a COVID-19-related ECMO indication, ELSO defined an age of more than 65 years as a relative and an even higher age as an absolute contraindication for ECMO initiation [ 43 ]. A recent retrospective study pointed out the importance of a patient-oriented and individualized approach in decision-making related to ECMO support initiation, arguing against the use of any age-related cutoffs [ 44 ]. In our work, an age of more than 60 years (median age of reported population), was associated with increased mortality (Additional file 1 : Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a COVID-19-related ECMO indication, ELSO defined an age of more than 65 years as a relative and an even higher age as an absolute contraindication for ECMO initiation [ 43 ]. A recent retrospective study pointed out the importance of a patient-oriented and individualized approach in decision-making related to ECMO support initiation, arguing against the use of any age-related cutoffs [ 44 ]. In our work, an age of more than 60 years (median age of reported population), was associated with increased mortality (Additional file 1 : Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, point-of-care lung sonography helps monitor an early fluid loading in ARDS [ 13 ] and antibiotic-induced pulmonary reaeration in ventilator-associated pneumonia [ 68 ]. In ARDS patients supported with an extracorporeal membrane oxygenation (ECMO), lung sonography allows for the monitoring of the disease course and may indicate eventual lung recovery, with the potential of early ECMO weaning initiation and a consequent improved patient outcome [ 69 , 70 ].…”
Section: Lung Sonography Signs Patterns and Clinical Interpretationmentioning
confidence: 99%
“…Despite immense research and development in the field of ECMO circuit technology in the last decades, a need for systemic anticoagulation therapy still exists. The potential improvement of the clinical outcomes of patients undergoing ECMO support depends on the underlying disease and comorbidities, the technology employed, and on anticoagulation [ 16 ].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Moreover, clinical studies should further narrow down the reported range of thrombosis incidence, which is perceived as one of the most important indications for anticoagulation. This holds especially true as bleeding increases mortality, but thrombosis does not [ 16 ].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation